Dynamic Capabilities in Volatile Markets: ‎Leveraging Strategic Flexibility and Customer ‎Insights to Drive Product Innovation and ‎Market Performance - Sam, Toong Hai; Mu'min, Halek; Kaihatu, Thomas Stefanus; Prihanisetyo, Adi; Pramono, Romy (International Journal of Accounting and Economics Studies, 2025)
This paper explores the use of dynamic innovation capabilities, understanding turbulences in the market, and enhancing customer ‎satisfaction to achieve product innovation and market performance in increasingly dynamic business environments. Following the dynamic ‎capabilities theory framework, this paper develops the following conceptual model to explore the interaction among dynamic innovation ‎capabilities, market turbulences, and customer satisfaction as antecedents to product innovation and the impact on market performance. Data ‎were collected from 287 manufacturing and technology managers. Results of the Structural Equation Model (SEM) provide evidence that ‎dynamic innovation capabilities, market turbulences, and customer satisfaction positively impact product innovation, which influences ‎market performance. This paper also provides evidence for the mediating role played by product innovation in the interrelationship among ‎the three antecedents and market performance. Consequences and implications for theory and management are offered to support ‎organizations in the formulation of appropriate strategies to counter uncertainties in the market‎.